EFEKTIVITAS PENERAPAN JAMINAN KESEHATAN NASIONAL MELALUI BPJS DALAM PELAYANAN KESEHATAN MASYARAKAT MISKIN DI KOTA PADANG - Putri, Nora Eka (Fakultas Ilmu Sosial Universitas Negeri Padang, 2014)
This study aims to assess the effectiveness of the implementation of the JKN program through BPJS in poor health services in the city of Padang. The mixed approach was used in this study with sequential explanation by distributing questionnaires to the respondents, followed by interviews with officials of BPJS Padang. The findings of this study indicated that the variable of effectiveness of JKN through BPJS have very strong relationships with the health services of the poor in the city of Padang. From the interviews it is known that the implementation of JKN program through BPJS for poor public health services in the city of Padang has not been effective. The effectiveness is not only seen from the quantitative targets but also based on the quality aspects of health services that includes the aspects of responsiveness, courtesy, credibility, and access. Key Words: Effectiveness, services, JKN BPJS, poor society